New media supervision, digital transformation, and corporate green investment - Zhang, Qixin; Xiang, Zhiqiang; Xiang, Zhiguo (Finance research letters, 2025)
•New media supervision has a significant promoting effect on corporate green investment.•Digital transformation plays a crucial mediating role in the influence between the two.•This impact is more prominent in the developed eastern regions. This research draws on data from Chinese A-share listed manufacturing enterprises spanning from 2009 to 2020, and explores the effect of new media supervision on corporate green investment. Analysis indicates that new media supervision exerts a substantial impetus on green investment, and the influence is even more pronounced under the mediation of digital transformation. Meanwhile, regional heterogeneity analysis shows that this influence is more prominent in developed eastern regions. Overall, through the exploration of the intersection between new media supervision and corporate green investment, this study can enrich the existing and continuously evolving understanding of corporate environmental investment.